Study of three interesting Amanita species from Thailand: Morphology, multiple-gene phylogeny and toxin analysis - Benjarong Thongbai (2018)
© 2017 Thongbai et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Amanita ballerina and A. brunneitoxicaria spp. nov. are introduced from Thailand. Amanita fuligineoides is also reported for the first time from Thailand, increasing the known distribution of this taxon. Together, those findings support our view that many taxa are yet to be discovered in the region. While both morphological characters and a multiple-gene phylogeny clearly place A. brunneitoxicaria and A. fuligineoides in sect. Phalloideae (Fr.) Quél., the placement of A. ballerina is problematic. On the one hand, the morphology of A. ballerina shows clear affinities with stirps Limbatula of sect. Lepidella. On the other hand, in a multiple-gene phylogeny including taxa of all sections in subg. Lepidella, A. ballerina and two other species, including A. zangii, form a well-supported clade sister to the Phalloideae sensu Bas 1969, which include the lethal “death caps” and “destroying angels”. Together, the A. ballerina-A. zangii clade and the Phalloideae sensu Bas 1969 also form a well-supported clade. We therefore screened for two of the most notorious toxins by HPLC-MS analysis of methanolic extracts from the basidiomata. Interestingly, neither α-amanitin nor phalloidin was found in A. ballerina, whereas Amanita fuligineoides was confirmed to contain both α-amanitin and phalloidin, and A. brunneitoxicaria contained only α-amanitin. Together with unique morphological characteristics, the position in the phylogeny indicates that A. ballerina is either an important link in the evolution of the deadly Amanita sect. Phalloideae species, or a member of a new section also including A. zangii.